The Dynamic Changes of the Plasma Membrane Proteins and the Protective Roles of Nitric Oxide in Rice Subjected to Heavy Metal Cadmium Stress - Yang, Liming; Ji, Jianhui; Harris-Shultz, Karen R.; Wang, Hui; Wang, Hongliang; Abd-Allah, Elsayed F.; Luo, Yuming; Hu, Xiangyang (Frontiers in Plant Science, 2016)
The heavy metal cadmium is a common environmental contaminant in soils and has adverse effects on crop growth and development. The signaling processes in plants that initiate cellular responses to environmental stress have been shown to be located in the plasma membrane (PM). A better understanding of the PM proteome in response to environmental stress might provide new insights for improving stress-tolerant crops. Nitric oxide (NO) is reported to be involved in the plant response to cadmium (Cd) stress. To further investigate how NO modulates protein changes in the plasma membrane during Cd stress, a quantitative proteomics approach based on isobaric tags for relative and absolute quantification (iTRAQ) was used to identify differentially regulated proteins from the rice plasma membrane after Cd or Cd and NO treatment. Sixty-six differentially expressed proteins were identified, of which, many function as transporters, ATPases, kinases, metabolic enzymes, phosphatases, and phospholipases. Among these, the abundance of phospholipase D (PLD) was altered substantially after the treatment of Cd or Cd and NO. Transient expression of the PLD fused with green fluorescent peptide (GFP) in rice protoplasts showed that the Cd and NO treatment promoted the accumulation of PLD in the plasma membrane. Addition of NO also enhanced Cd-induced PLD activity and the accumulation of phosphatidic acid (PA) produced through PLD activity. Meanwhile, NO elevated the activities of antioxidant enzymes and caused the accumulation of glutathione, both which function to reduce Cd-induced H2O2 accumulation. Taken together, we suggest that NO signaling is associated with the accumulation of antioxidant enzymes, glutathione and PA which increases cadmium tolerance in rice via the antioxidant defense system.